2018
DOI: 10.1111/jfs.12509
|View full text |Cite
|
Sign up to set email alerts
|

RFLP analysis of flagellin (Fla) gene of Campylobacter jejuni from ovines of Kashmir, India

Abstract: Campylobacteriosis caused by Campylobacter jejuni is the most frequently reported foodborne illness transmitted directly or indirectly between animals and humans. Humans can be infected after ingesting undercooked poultry and other meats, raw milk, raw clams, contaminated foodstuffs etc. In the present study sheep breeding farms of Kashmir valley were screened for presence of Campylobacter jejuni, and C. coli. infection. Of the 200 samples comprising of vaginal swabs and aborted material 25(12.5%) isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Whereas 58 of 200 samples (29%) were detected positive by PCR, only 11 (5Á5%) isolates were detectable by culture. This low detection could be due to fastidious growth requirement of organism (Gull et al 2018). Of the tested animals, 42Á2% of cows were positive but only 1Á5% bulls were positive by culture (by PCR, these fractions were 48 and 3%, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…Whereas 58 of 200 samples (29%) were detected positive by PCR, only 11 (5Á5%) isolates were detectable by culture. This low detection could be due to fastidious growth requirement of organism (Gull et al 2018). Of the tested animals, 42Á2% of cows were positive but only 1Á5% bulls were positive by culture (by PCR, these fractions were 48 and 3%, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…The prevalence of Campylobacter spp. was 9.33% in sheep in the coastal region of Odisha, India [ 38 ] and 12.5% in Kashmir, India, according to vaginal swabs and aborted material examination [ 39 ]. The findings of these studies corroborated with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…No samples were positive for wlaN. Bisma et al (2018) also reported the presence of the virulence genes fla, cdt, and cad in seventeen isolates of C. jejuni and three isolates of C. coli.…”
Section: Cases From Veterinary Hospitalsmentioning
confidence: 93%
“…C. jejuni (1%) was only isolated from vaginal swabs of the healthy animals. Several studies (Hamali et al 2014, Bisma et al 2018 have reported the presence of C. jejuni and C. fetus subsp. fetus from the vaginal swabs and aborted samples.…”
Section: Cases From Veterinary Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation